2014
DOI: 10.1155/2014/808012
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Pattern of CXCR4 Expression Is Associated with a Better Overall Survival in Patients with Gastric Cancer

Abstract: Introduction. Previous studies have shown that stromal-derived factor-1 (CXCL12) and its receptor, CXCR4, play a crucial role in metastasis of various tumors. Similarly, it has been cleared that CXCR4 is expressed on the cell surface of gastric cancers. However, nuclear expression of CXCR4 and its clinical importance have not been yet studied. Materials and Methods. Herein, we studied the expression of CXCR4 in gastric samples from patients with gastric adenocarcinoma as well as human gastric carcinoma cell li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 24 publications
0
12
1
Order By: Relevance
“…CXCL12 and CXCR4 are usually predominantly expressed on cell membrane or in the cytoplasm, although CXCL12 can also be secreted as a soluble form and CXCR4 sometimes still appears in the nucleus of GC cells . In AGS cells, CXCR4 has been identified at high levels in both cytoplasm and nucleus, but low on cell membrane . KATO III cell line similarly expresses low level of membrane CXCR4, which shows specific migratory but no proliferative or anti‐apoptotic activities in response to CXCL12 .…”
Section: Expression Of Cxcl12/cxcr4 Axis In Gcmentioning
confidence: 99%
See 1 more Smart Citation
“…CXCL12 and CXCR4 are usually predominantly expressed on cell membrane or in the cytoplasm, although CXCL12 can also be secreted as a soluble form and CXCR4 sometimes still appears in the nucleus of GC cells . In AGS cells, CXCR4 has been identified at high levels in both cytoplasm and nucleus, but low on cell membrane . KATO III cell line similarly expresses low level of membrane CXCR4, which shows specific migratory but no proliferative or anti‐apoptotic activities in response to CXCL12 .…”
Section: Expression Of Cxcl12/cxcr4 Axis In Gcmentioning
confidence: 99%
“…As for MKN‐28, MKN‐45, MKN‐74, and SNU‐16 cells, CXCR4 is abundant in the cytoplasm but absent on cell membrane, which results in neither migratory, nor proliferative and survival responses to CXCL12 . In primary GC tissues, CXCR4 is generally strongly expressed in both the cytoplasm and the nucleus . But in diffuse‐type GC, including signet‐ring cell carcinoma, CXCR4 staining is usually seen in the nucleus and scant in the cytoplasm .…”
Section: Expression Of Cxcl12/cxcr4 Axis In Gcmentioning
confidence: 99%
“…Downregulation of SDF-1 α also has been reported in colonic carcinoma [21] and human astrocytoma [22]. In continuation with these reports, Nikkhoo et al [23] have demonstrated recently that nuclear expression CXCR4 is associated with a better overall survival of patients with gastric cancer. These literatures regarding CXCR4 indicate that CXCR4 signaling is not limited to promote tumor progression only; it is also involved in maintaining normal homeostasis of cells/tissue.…”
Section: Introductionmentioning
confidence: 75%
“…Discrepancies between chemokine expression by immunohistochemical evaluation and mRNA level have been reported. 18,31 Last, and most important, increased chemokine receptor expression in the primary tumor may be sufficient for homing to the metastatic site with no need for further upregulation upon arrival.…”
Section: Discussionmentioning
confidence: 99%